(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article presents some discussions about visuality constructed on the artistic happening, by the light performativity considering its relation with its actuator, being this an actor, performer, light operator, spectator, and/or inter author of the poetic action. Thus, the research dialogues with the transformations of the artistic act catapulted by postmodernity and the adventurous of contemporary art. In this context, it seeks for understanding light supposedly as a performative object, to create, by lightning and expressive and autonomous field while language.